1997
DOI: 10.2166/wst.1997.0003
|View full text |Cite
|
Sign up to set email alerts
|

The bioaugmentation of sequencing batch reactor sludges for biological phosphorus removal

Abstract: The development of enhanced biological phosphorus removal (EBPR) through the bioaugmentation of a conventional activated sludge was studied. The objectives of the study were to evaluate the phosphorus removal capability of a sequencing batch reactor (SBR) when started with conventional activated sludge and augmented with a pure culture of Acinetobacter lwoffii. The effect of the addition of the pure culture on the reactor start up time, the settling properties of the sludge and on COD and nitrogen removal was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
8
1
1
Order By: Relevance
“…COD removal and methane production were the same between the reactor bioaugmented by adsorption (R4) and the one bioaugmented by encapsulation (A3). This is in contrast with the results of Belia and Smith (1997), who observed that their bioaugmented sequencing-batch reator had the same COD removal than their control reactor. This work demonstrated that the removal of a mixture of phenolic compounds can be improved in UASB reactors using bioaugmentation with an acclimatized consortium.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…COD removal and methane production were the same between the reactor bioaugmented by adsorption (R4) and the one bioaugmented by encapsulation (A3). This is in contrast with the results of Belia and Smith (1997), who observed that their bioaugmented sequencing-batch reator had the same COD removal than their control reactor. This work demonstrated that the removal of a mixture of phenolic compounds can be improved in UASB reactors using bioaugmentation with an acclimatized consortium.…”
Section: Discussioncontrasting
confidence: 99%
“…They have demonstrated that, in a sequencing-batch reactor, the addition of Pseudomonas putida PRS 2015 pAC27 to activated sludge degraded completely 160 mg/L of 3-chlorobenzoate after 8 d, compared to 13 d for a non-augmented bioreactor. Using the same process, Belia and Smith (1997) augmented an activated sludge with a pure culture of Acinetobacter lwoffii to enhance biological phosphorus removal. They showed that the bioaugmented reactor attained 90% phosphorus removal in 14 d, while the control reactor took 6 to 7 weeks to reach the same performance.…”
Section: Discussionmentioning
confidence: 99%
“…Bioaugmentation is recognized as a promising and attractive operational means to strengthen wastewater treatment performance [3,4] and has been demonstrated to successfully enhance the degradation and removal of specific pollutants such as phenols [5], 3-chloroaniline [6], phosphate [7], and aromatic hydrocarbons [4,8]. However, it does not always work, and the treating effects of bioaugmentation have been reported to be less predictable and controllable [3].…”
Section: Introductionmentioning
confidence: 99%
“…12 a 25 semanas. Sin embargo, existen estudios a nivel de laboratorio, realizados con agua residual sintética enfocados a la reducción del período de arranque del sistema de fangos activos que indican que incorporando fango aclimatado al proceso de EBF, el tiempo de aclimatación se puede reducir a 5 días, y a 2 semanas empleando una cepa de Acinetobacter lwoffi (Belia y Smith, 1997). Podemos finalizar resumiendo las caracteristicas más importantes del proceso de eliminación biológica de fós-foro.…”
Section: Resumen Y Discusiónunclassified